2018
DOI: 10.1177/0020872818776726
|View full text |Cite
|
Sign up to set email alerts
|

The effect of social capital on non-suicidal self-injury and suicidal behaviors among college students in Greece during the current economic crisis

Abstract: This cross-sectional study examines the effects of social capital on non-suicidal self-injury and self-injurious behaviors among 632 Greek college students during the current economic crisis. This is a quantitative study which uses a set of normed instruments to measure non-suicidal self-injury and suicidal behaviors. After controlling for a set of demographic variables, and negative affective states, social capital was not found to have an effect on non-suicidal self-injury or suicidal behaviors ( p > .05)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 72 publications
(111 reference statements)
0
3
0
Order By: Relevance
“…Higher subscale scores reflect higher levels of depression, anxiety, and stress in the past week, with a higher sum score representing greater general distress. DASS has been used widely with college populations (Koutra et al, 2020). The Greek translation of the DASS is both reliable and valid, with psychometric properties close to those reported in the international literature as determined by Cronbach's alpha .97.…”
Section: Depression Anxiety Stress Scale -21 (Dass-21)mentioning
confidence: 71%
“…Higher subscale scores reflect higher levels of depression, anxiety, and stress in the past week, with a higher sum score representing greater general distress. DASS has been used widely with college populations (Koutra et al, 2020). The Greek translation of the DASS is both reliable and valid, with psychometric properties close to those reported in the international literature as determined by Cronbach's alpha .97.…”
Section: Depression Anxiety Stress Scale -21 (Dass-21)mentioning
confidence: 71%
“…Research in the period of Covid 19 (Giavrimis & Nikolaou, 2020) on students' social and friendship networks and how they affected students in the midst of a pandemic, found that high social capital can create the right conditions for positive social relationships and interactions of students, for the development of social trust, as a necessary condition for cooperation, productive action and peer behavior. The consequences of the high social capital of students in the pandemic period were particularly positive, emphasizing once again that the development of social and friendly networks and social interaction for the development of initiatives and social trust are key elements of human existence (Almeida et al, 2019;Peng, 2019;Mishra, 2020;Koutra et al, 2020).…”
Section: Discussion Of the Resultsmentioning
confidence: 99%
“…Self-concept is among the most important factors influencing especially girls' health in this period. Adolescence, due to the internal and external changes, is one of the most sensitive and critical stages of life (1), which can lead to evolutional crisis and disturbing individual balance and emergence of new demands (2,3).…”
Section: Introductionmentioning
confidence: 99%